The rise of populist electoral politics 1990 - 2020: a comparative political geography of the Economic Freedom Fighters and the Rassemblement National - Stewart, SL (2022)
This work draws on scholarly agreement about the core features of populism, which have made populism an analytically useful term, to examine the rise of contemporary populism and populist electoral politics in neoliberal democracies of the global North and the global South. The core features of populism include claims to one leader, one people and one (popular) will. These features are used as the ontological and definitional basis of the study. Considering longstanding debate about the conditions under which populism is likely to succeed and “the people” to whom populism refers, the thesis goes beyond ‘supply-side’ theories of populist politics to interrogate the ‘demand-side’ of populist electoral politics. Whereas work on populism per se remains episodic and fragmentary in Geography, this thesis mobilises case studies and literatures in human and political geography, including the political geography of the state, labour geography, and military geographies to contribute to a spatialised theorisation of contemporary populist electoral politics.